MOSAIC a multiwavelength optical subcarrier multiplexed controlled network. - Gaudino, R.
The experimental demonstration of MOSAIC, a reconfigurable WDM add/drop network with subcarrier multiplexed control, is presented. The MOSAIC network implements the optical layer protocol to support bit-rate transparent multichannel lightpaths. Two types of add/drop multiplexers are implemented and combined in a three-node experiment. Multihop lightpaths are established giving an end-to-end bit error rate of better than 10-9 at 1.2 Gbps. The reconfigurable add/drop multiplexer is based on a novel dilated 2×2 acoustooptic filter switch crossconnect and an analog optoelectronic crossconnect that drives a ten-wavelength laser array transmitter up to 2.5 Gbps per wavelength. The fixed wavelength add/drop multiplexer utilizes a fast digitally tunable laser transmitter. Both add/drop multiplexers support bit-rate transparent 2R optoelectronic regeneration as well as wavelength translation. Subcarrier multiplexing on each wavelength is used to support channel state monitoring and channel equalization as well as transmission of digital network control information. Systems experiments demonstrate cascaded 2R optoelectronic regeneration with wavelength translation and cascaded multichannel optical switching with up to seven hops. It is shown that combining cascaded 2R optoelectronic regeneration with cascaded multichannel optical switching can be used to balance jitter accumulation and amplified spontaneous emission generated amplitude noise to yield high signal-to-noise ratio for lightpaths
Keywords: 1.2 Gbit/s.; 2.5 Gbit/s.; MOSAIC network; SNR; Acoustooptic filter switch crossconnect; Amplified spontaneous emission; Amplitude noise; Analog optoelectronic crossconnect; Bit error rate; Bit-rate transparent multichannel lightpaths; Cascaded 2R optoelectronic regeneration; Cascaded multichannel optical switching; Channel equalization; Channel state monitoring; Digital network control; Experimental demonstration; Fast digitally tunable laser transmitter; High signal-to-noise ratio; Jitter accumulation; Laser array transmitter; Multihop lightpaths; Multihop lightpaths; Multiwavelength optical subcarrier multiplexed controlled network; Optical layer protocol; Reconfigurable WDM add/drop network; Reconfigurable add/drop multiplexer; Subcarrier multiplexed control; Wavelength translation